Analysis of the mucosal immune responses induced by single and trickle infections with the bovine abomasal nematode Ostertagia ostertagi. (April 2014) - Mihi, B.; van, F.; Vancoppernolle, S.; Rinaldi, M.; Chiers, K.; van den, W.; Goddeeris, B. M.; Vercruysse, J.; Claerebout, E.; Geldhof, P.
Summary The purpose of this study was to provide more information on the kinetics of the immunological changes occurring in the abomasal mucosa after single and trickle infections with the bovine parasite Ostertagia ostertagi. The time course analysis of gene expression revealed that the major changes coincided with the emergence of adult worms from the gastric glands. These changes consisted of a simultaneous upregulation of Th1‐ and Th2‐type cytokines. In addition, a single O. ostertagi infection elicited an upregulation of the epithelial‐derived cytokine IL33, while TSLP expression levels were not impacted. Apart from the massive increase in inflammatory cytokines IL6, IL17 and IL21, O. ostertagi infection also elicited an upregulation of the immunosuppressors TGFB, IL10 and ARG1, as well as NK and γδ‐T cell markers. Furthermore, the cytotoxic factors granulysin, perforin and granzyme B were upregulated following an O. ostertagi infection. Analysis of cytokine transcript levels in animals receiving trickle infections for 60 days showed a similar trend as observed following a single infection except for IL33, IL6, GATA‐3, TBX21 and NCR1, which were no longer upregulated after trickle infections. Finally, the long trickle infections were associated with mucosal eosinophilia and mastocytosis.